Implementasi Algoritma MD4 Pada Aplikasi Duplicate Audio Scanner - Astuti, Tri Windi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Nowadays there are many applications that help the process of duplicating audio, of course this takes up more storage space. For that we need a method that can be used to identify the same or duplicate audio files. The solution that can be done to handle duplication of audio files or duplicates is to apply hash type cryptography techniques where the process of identifying the hash value of the audio file is carried out so that the resulting value is different from the original file. The hash type cryptographic algorithm used is the MD4 algorithm. The results obtained from the process of applying the MD4 algorithm are grouping audio files based on the same hash value, making it easier and faster for users to delete duplicate audio files